A new species of the rare nematode genus Margollus Peña-Santiago, Peralta & Siddiqi, 1993 (Nematoda: Tylencholaimoidea) from Turkey - Ahmad, Wasim; Ahad, Sumaya; Sturhan, Dieter (Zootaxa, 2013)
Margollus turcicus sp. n., is described and illustrated from vineyard soil in Turkey. The new species is characterized by having a medium sized body (L=1.0–1.2 mm); cuticle with distinct striations; radial refractive elements abundant; lip re-gion distinctly narrower than the adjoining body and slightly offset from the body contour by a depression; cephalic and labial papillae not discernible; strong labial and post-labial sclerotization present; amphids well developed with sclero-tized walls; stylet 27–28.5 μm long, odontophore distinctly flanged, 0.3 times the odontostyle length; pharyngeal bulb off-set by constriction, 33–37 μm long; mono-opisthodelphic female genital system with anterior branch 22–41 μm long; spicules 49 μm long; single weak ventromedian supplement and short hemispheroid tail in both sexes.